Determination of the influence of the control parameters of the stepper drive for rotating the platform for a gas-detonation mortar on its electrical and mechanical performance - Liubarskyi, Borys; Kryvosheiev, Serhii; Eresko, Oleksandr; Halytsia, Vitalii; Sakun, Oleksandr; Liubarskyi, Dmytro (Technology audit and production reserves, 2025)
The object of research is the processes of platform rotation during the operation of the stepper drive of a gas-detonation powderless mortar. The problem solved by the study is to determine the influence of the set current and the rotation frequency of the stepper motor for the rotation of the platform for a gas-detonation mortar on the effective value of the phase current, vibration and maximum engine torques. According to the results of the research, it was determined that the effective value of the phase current has a variable character. The minimum value of the effective phase current is observed at a rotation frequency of 52.5 rpm, and a set current of 5.5 A, and is 0.875 A. The obtained dependence of the effective current on the control parameters has a non-monotonic variable character, due to a change in the shape of the current during engine operation, which, in turn, significantly changes the harmonic composition of the current. The dependence of the vibration torque of the engine also has a variable character. However, the minimum vibration is observed at a rotation frequency of 45 rpm, and a set current of 5 A, and is 7.715 N ⋅ m, and the maximum vibrations at the minimum operating frequency and the maximum setpoint current reach 39.72 N ⋅ m. The dependence of the maximum torque value on the stepper motor shaft has a decreasing character, due to the operation of the drive in the starting mode. The decrease in the starting torque is due, on the one hand, to a decrease in the setpoint current, and, accordingly, to the maximum motor current and an increase in the electromotive force in phase with an increase in the setpoint speed. The obtained research results can be used in practice when creating an automated electric drive for turning a gas-detonation mortar based on a stepper motor by selecting the parameters of the setpoint current for the semiconductor converter, in accordance with the rotation speed. The conducted research can be used as the basis for the methodology for determining the control parameters of the electric drive for turning based on a stepper motor.